Impact of flight speed distribution on efficiency of urban air traffic network - Gong, Tingyu; Nnamani, Christantus O.; Xu, Yan; Tsourdos, Antonios (Institute of Electrical and Electronics Engineers (IEEE), 2023)
The emerging Urban Air Mobility (UAM) completes the current urban transportation landscape along with surface transport and relieves road traffic congestion significantly. This relief is not only to add one or more available ways in the air above each existing roadway, but to improve the operating efficiency of the entire traffic network by leveraging electric vertical take-off and landing (eVTOL) aircraft and exploiting advanced air traffic management technologies and procedures. The urban air traffic network is constructed in two different topological structures, namely generalized topology taking airway segments as edges and intersections between two airway segments as nodes, and dual topology considering airways as nodes and connection relationships between two airways as edges. Flight speed is assigned as weight to either airway segment or the entire airway in the two topology networks and network efficiencies are investigated with five common distributions of weight. A method of weight randomization is applied to further explore the impact of weight distribution on both networks, and the results demonstrate that the global and local network efficiencies of a regular network increase with various weight distributions to a certain degree, indicating that network efficiency can be improved by adjusting flight speed distribution while not changing the network structure. The comparison of the experiments on the two topology networks reveals that such adjustment is better-performed segment by segment instead of airway by airway, which provides a reference for stakeholders to manage the urban air traffic flow via better control of flight speed.
Keywords: Urban air mobility; Network efficiency; Urban air traffic management; eVTOL aircraft